Safety and Efficacy of CR6261 in an Influenza A H1N1 Healthy Human Challenge Model. (19th November 2020) - Han, Alison; Czajkowski, Lindsay; Rosas, Luz Angela; Cervantes-Medina, Adriana; Xiao, Yongli; Gouzoulis, Monica; Lumbard, Keith; Hunsberger, Sally; Reed, Susan; Athota, Rani; Baus, Holly Ann; Lwin, Amy; et al.
Abstract: Background: It is imperative to identify new targets for improved vaccines and therapeutics against influenza. One such target is the relatively conserved stalk region of the influenza A hemagglutinin (HA) surface protein. Methods: We conducted a randomized, double-blind, phase 2, placebo-controlled trial of a monoclonal antibody that targets the HA stalk (CR6261) in a H1N1pdm09 healthy volunteer human challenge model. A single 50 mg/kg dose of CR6261 was infused 24 hours after challenge. The primary efficacy outcome was area under the curve (AUC) of viral RNA detection over time. Results: Ninety-one healthy volunteers were randomized and underwent influenza challenge; 49 received CR6261 and 42 received placebo. CR6261 had no statistically significant effect on AUC (AUC, 48.56 log [copies/mL] × days, interquartile range [IQR], 202 vs AUC, 25.53 log [copies/mL] × days, IQR, 155; P = .315) and no clinically significant effect on influenza disease measures including number of symptoms, duration of symptoms, or inFLUenza Patient-Reported Outcome (FLU-PRO) scores. Preexisting anti-NA antibody titers were most predictive of reduced influenza disease. CR6261 reached a mean peak serum concentration of 1 × 10 6 ng/mL 15 minutes after infusion and a mean peak of 5.97 × 10 2 ng/mL in the nasal mucosa 2–3 days after infusion. Conclusions: The results of this study suggest that a monoclonal anti-stalk approach to prevent or treat influenza infection may be limited in efficacy. Future approaches should consider including and evaluating anti-stalk antibodies as part of a multifaceted strategy rather than as a stand-alone therapeutic. Clinical Trials Registration: NCT02371668. Abstract : Administration of intravenous monoclonal antibody CR6261 24 hours after influenza challenge was found to be safe, although it had no effect on viral replication or influenza severity among healthy volunteers.